Maternal responses to negative infant cues of Filipino mothers from selected urban poor communities - Cadag, Monique Angela O.; Samson, Bea Leslyn L. (College of Home Economics, University of the Philippines Diliman, 2019)
This study seeks to identify the different attitudes, emotions, and actions of urban poor mothers towards the negative cues of their infant. Moreover, the study aims to explore the facilitating and limiting factors to these responses. The selected urban poor communities were Barangay San Vicente, Sitio Lambak (Barangay Krus na Ligas) and Pook Dagohoy (Barangay UP Campus). A total of thirty respondents were subjected to an in-depth interview to ask narrations on their experiences with their infant's negative cues. Data were encoded, selected, and categorized based on salient themes. Results of the study shows mothers' actions and emotions vary depending on their perception of their infant's negative cues. Their emotional responses also differ depending on the context of these cues. For instance, mothers get frustrated at their infant's inconsolable crying and night waking, however, feels pity and worry if these are cues pertaining to an illlness. Factors such as presence of secondary or tertiary caregivers, guidance from their own mothers, and previous caregiving experiences aids mothers in responding to their infants while mother's responsibilities aside from caregiving and financial constraints were identified as limiting factors. Despite these, results of the study show that urban poor mothers consider their caregiving role as their priority, hence they would always find a way to respond to their infant's negative cues despite the different challenges or limitations they are facing.